Therapeutic Strategies Aimed at Improving Neuroplasticity in Alzheimer Disease - Colavitta, María Florencia (2023)
Este artículo pertenece a un número especial llamado "New Discoveries in Drug Targets and Delivery for Alzheimer’s Disease", que se puede consultar desde el siguiente enlace: https://www.mdpi.com/journal/pharmaceutics/special_issues/30TR5812B9